The effect of diaphragm contraction on upper airway collapsibility - Hillman, D.; Walsh, J.; Maddison, K.; Platt, P.; Schwartz, A.; Eastwood, Peter (2013)
Increasing lung volume increases upper airway patency and decreases airway resistance and collapsibility. The role of diaphragm contraction in producing these changes remains unclear. This study was undertaken to determine the effect of selective diaphragm contraction, induced by phrenic nerve stimulation, on upper airway collapsibility and the extent to which any observed change was attributable to lung volumerelated changes in pressure gradients or to diaphragm descent-related mediastinal traction. Continuous bilateral transcutaneous cervical phrenic nerve stimulation (30 Hz) was applied to nine supine, anesthetized human subjects during transient decreases in airway pressure to levels sufficient to produce flow limitation when unstimulated. Stimulation was applied at two intensities (low and high) and its effects on lung volume and airflow quantified relative to unstimulated conditions. Lung volume increased by 386 ± 269 ml (means ± SD) and 761 ± 556 ml during low and high stimulation, respectively (P < 0.05 for the difference between these values), which was associated with peak inspiratory flow increases of 69 ± 57 and 137 ± 108 ml/s, respectively (P < 0.05 for the difference). Stimulation-induced change in lung volume correlated with change in peak flow (r = 0.65, P < 0.01). Diaphragm descent-related outward displacement of the abdominal wall produced no change in airflow unless accompanied by lung volume change. We conclude that phrenic nerve stimulationinduced diaphragm contraction increases lung volume and reduces airway collapsibility in a dose-dependent manner. The effect appears primarily mediated by changes in lung volume rather than mediastinal traction from diaphragm descent. The study provides a rationale for use of continuous phrenic stimulation to treat obstructive sleep apnea. Copyright © 2013 the American Physiological Society.